Strategy Workshops and Strategic Change - Robert MacIntosh; Donald MacLean; David Seidl (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2008)
Despite the attention that strategic change as a topic of research has received, there remain considerable difficulties in conceptualizing the actual sources of strategic change. Strategy workshops represent one obvious and explicit research site since organizations often use such events as a means of effecting or initiating strategic change. This paper examines empirical data from ninety-nine strategy workshops in ten separate organizations to address the research question: Do strategy workshops produce strategic change? The paper concludes that workshops can produce change but that one-off workshops are much less effective than a series of workshops. The data presented indicates that the elapsed duration of the entire series of workshops, the frequency of workshops, the scope and autonomy of the unit concerned, and the seniority of participants have an impact on the success or failure of the venture.
urn:nbn:de:bvb:19-epub-2145-6
Keywords: 650; Co-production of Knowledge; Engaged Scholarship; Strategic Change; Strategy as Practice; Strategy Workshops